Implementation of SIAKBA by the Bekasi City General Elections Commission (KPU) in Enhancing the Human Resources of the Ad Hoc Body for the 2024 Regional Head Elections - Afif Fauzi; Veithzal Rivai Zainal; Azis Hakim (Jurnal Ekonomi Manajemen Sistem Informasi, 2025)
The Bekasi City General Election Commission (KPU) has conducted the recruitment of 60 Sub-District Election Committee (PPK) members using the KPU and Ad Hoc Body Member Information System (SIAKBA). Referring to the utilization of this application by the Bekasi City KPU, the author is interested in discussing the implementation of SIAKBA at the Bekasi City KPU in enhancing the human resources of the Ad Hoc Election Body for the 2025 Regional Head Election. This study is qualitative and descriptive-analytical in nature. The findings indicate that in the recruitment practice of the Sub-District Election Committee (PPK) for the Bekasi City Regional Head Election, the KPU and Ad Hoc Body Member Information System (SIAKBA) plays a crucial role as a digital gateway that guides the selection process towards objective, transparent, and measurable standards. This mechanism demonstrates the practical application of the "fit for the job" principle, where recruitment is no longer solely based on social relations or administrative approaches but rather on technical competence, relevant work experience, and personal integrity aligned with the job functions. Furthermore, the automated and digital recording within SIAKBA enables managers or administrators within the KPU environment to systematically conduct monitoring, evaluation, and performance trend analysis based on data.